Luís da Silveira y la ficción sentimental Naseo e Amperadonia - Tarrío, Ana María S. (2021)
This study brings together a set of arguments in favour of the attribution of the sentimental novel Naseo e Amperadonia to the poet of the Cancioneiro Geral Luís da Silveira (1483-1534), guarda-mor of prince D. João and future king D. João III, Count of Sortelha, among other titles. This authorship emerges in a copy discovered by H. Sharrer in the Ajuda Library (Ms. 51-VI38). The novel had hitherto been considered anonymous and was known only from a copy preserved in a miscellaneous codex so-called “Asensio’s manuscript”. The analysis of the two versions leads us to the conclusion that the Ajuda copy, although made at a later period than Asensio’s copy, conveys an earlier stage of the novel. In the Asensio’s manuscript, the author’s name and the name of the main addressee (João Rodrigues de Sá de Meneses) were removed; the happy ending to the love story was also amputated. In addition, there are other kind of interventions aimed at stylistic purification in relation to the stage of the text offered in the Ajuda copy. These pages also propose new arguments about the location of the action in the Turkish East in the light of Manueline war campaigns in the East at the time of Silveira, as well as presenting other significant concomitances between the novel and the compositions published in the Cancioneiro Geral by Silveira and his main interlocutor João Rodríguez de Meneses.